La structure urbaine en république Argentine : le cas de Buenos Aires - Denis, Paul-Yves (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1967)
Approximately one half of Argentina’s population is found along an axis extending between the cities of Rosario and La Plata, and which includes only 3 per cent of the national territory. Because of this striking concentration, Buenos Aires's metropolitan function is of ever-increasing importance ; with its seven million inhabitants, it bas a virtual monopoly of the secondary and tertiary activities of the country. But this lack of equilibrium, and the city's off-centre location, have made necessary the decentralization of both industry and government. The development of five large centres — Córdoba, Mendoza, Tucumán, Santa Fe — Paraná, and Resis-tencia — Corrientes — have permitted the establishment of a better balanced urban structure and national economy.